2019
DOI: 10.1063/1.5111633
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentation of an elliptic rigid particle in a yield-stress fluid: A Lattice-Boltzmann simulation

Abstract: Sedimentation of a single, two-dimensional, rigid, elliptic particle in a biviscous fluid contained in a finite, closed-ended channel is studied in this work using the lattice-Boltzmann method. The main objective of the work is to numerically investigate the role played by a fluid’s yield stress on the trajectory, orientation, and terminal velocity of such a particle for different density and aspect ratios. Numerical results suggest that a new mode of settling might emerge for yield-stress fluids, which is non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In this proceeding, the authors show a slight reduction in angular velocity that diminishes with particle aspect ratio. Sobhani et al [46] also studied the dynamics of an elliptic particle in a yield-stress fluid using the lattice-Boltzmann method. In this paper we consider the dynamics of a neutrally buoyant three-dimensional prolate spheroid in a shear flow of a weakly shear-thinning fluid.…”
Section: Introductionmentioning
confidence: 99%
“…In this proceeding, the authors show a slight reduction in angular velocity that diminishes with particle aspect ratio. Sobhani et al [46] also studied the dynamics of an elliptic particle in a yield-stress fluid using the lattice-Boltzmann method. In this paper we consider the dynamics of a neutrally buoyant three-dimensional prolate spheroid in a shear flow of a weakly shear-thinning fluid.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we used the Herschel-Bulkley model as a model that can express a non-Newtonian solvent [13,24]. This model can change solvent properties by changing the power-law index n and Bingham number Bn.…”
Section: Herschel-bulkley Modelmentioning
confidence: 99%
“…As mentioned above, many studies have used a Newtonian fluid as a solvent, and power-law fluid has often been used in the studies about non-Newtonian fluid. On the other hand, in a study using a solvent that had yield stress in a channel flow, Sobhani et al [13] suggested that the equilibrium position of the rigid elliptical particle in Bingham fluid was different from that in Newtonian fluid when the particle with gravity settled. Furthermore, Chaparian et al [14] reported that Bingham fluid affected the equilibrium position when elastoviscoplastic fluid was used.…”
Section: Introductionmentioning
confidence: 99%
“…There are also other complex simulations using approaches such as the Masliyah-Lockett-Bassoon (MLB) model, 19,27 force coupling method (FCM), 28 effective-medium model, 29 or effective voidage model 30 to predict the settling velocities of two interfaces, which require significant computation time. Furthermore, the settling of different shaped particles, in particular ellipses, 31,32 has been simulated to establish the dynamics of systems with wider application. Other nonspherical particles such as rods 33,34 are also drawing attention in recent years and are more oriented toward industrial applications such as pharmaceuticals.…”
Section: Simulation Of Bidisperse Colloidal Centrifugal Sedimentation...mentioning
confidence: 99%